Effect of calcination temperature on the catalytic activity of zirconia-supported heteropoly acids - Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Zirconia-supported silicotungstic acid (15% STA) catalyst with different calcination temperatures (600-850 degrees C) was prepared by suspending zirconium oxyhydroxide in methanol solution of STA followed by drying and calcination. These catalysts were characterized by XRD, FTIR pyridine adsorption and DRUV-vis spectroscopy. The catalysts showed both Bronsted as well as Lewis acidity and 15% STA on zirconia calcined at 750 degrees C (15 SZ-750) had the highest Bronsted acidity. Characterization of 15 SZ-750 catalyst by Raman spectroscopy showed the presence of zirconia-anchored mono-oxotungstate as the major tungsten species present in this catalyst. These catalysts were used in benzoylation of veratrole with benzoic anhydride and 15 SZ-750 catalyst showed the highest activity. For catalyst with support calcined at different temperatures before HPA impregnation, catalytic activity decreases as the support calcination temperature increases due to the decrease in Bronsted acidity. Comparison of the catalytic activity of 15 SZ-750 with that of zirconia-supported phosphotungstic acid (15%, calcined at 750 degrees C, 15 PZ-750) in benzoylation of veratrole with benzoic anhydride, acylation of anisole with acetic anhydride and in alkylation of diphenylether with 1-dodecene showed that 15 SZ-750 catalyst has higher activity and deactivation resistance due to its higher Bronsted acidity. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Alkylation; Anisole; diphenylether; Phosphotungstic acid; Silicotungstic acid; veratrole; Zirconia